Anticipated work-family conflict amongst female business students: The influence of parental role modelling - Schwartz, Tamlyn (School of Management Studies, 2018)
For many young women, the transition from late childhood to early adulthood is a challenging time (Arnett, 2000). It is a time spent exploring different career opportunities and relationships and considering future family aspirations. Thinking about one’s future work and family can evoke many concerns amongst emerging adults, especially female students who plan to pursue demanding careers. This is a global phenomenon and South African female students are no exception (Bagraim & Harrison, 2013). Anticipated work-family conflict (AWFC) has received some attention amongst researchers due to the potential impact AWFC can have on students’ decision making (Barnett, Gareis, James, & Steele, 2003; Coyle, Van Leer, Schroeder, & Fulcher, 2015; Michael, Most, & Cinamon, 2011; Westring & Ryan, 2011). Over the past few decades, there has been a global increase in women entering the workforce (Blau & Kahn, 2007; Goldin, 2014). This has resulted in an increase in dual-earner families as both men and women have become co-breadwinners. Despite a shift in shared work responsibilities, many women still feel that taking care of their family is their primary responsibility (Askari, Liss, Erchull, Staebell, & Axelson, 2010). The added pressure that women experience in balancing both work and family domains highlights the importance of better equipping female students with the necessary resources and support as they transition into early adulthood. Not all students experience the same levels of AWFC (Barnett et al., 2003; Coyle et al., 2015). Identifying the key contributors to students’ AWFC has therefore generated a small body of research, which still requires further development. The limited research on students’ perceptions of the work-family interface includes research on several influencing factors, such as gender (e.g. Weer, Greenhaus, Colakoglu, & Foley, 2006); maternal employment (Barnett et al., 2003; Weer et al., 2006), parental education (O'Shea & Kirrane, 2008), self-efficacy to manage future work-family conflict (Cinamon, 2006) and parental role sharing of childcare and housework (Cinamon, 2006). A common thread across the literature is the influence of parents on their children’s perceptions of work and family. Socialisation into the work-family interface begins from early childhood and continues beyond adolescence, with parents shaping their children’s views of work and family life (Levine & Hoffner, 2006; Wiese & Freund, 2011).